Cabang-Cabang Ilmu Hadis - Dairina Yusri (Sekolah Tinggi Agama Islam Sumatera Medan, 2017)
Ulūmul hadith is aprayer one very religious disciplines, especially once to review the study and master of hadith operates Good and right. Judging from its fungtions Ulūmul hadith has important role against tradition as well as the position Ulūmul against Qur’an. Trus article search between Ulūmul hadith traditions and a very close relationship. Therefore the world life herth underwent happiness and the hereafter muslims must lean addressed to the Islamic law the first and main fence namely Qur’an and al-hadith.